The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4149/bll_2018_089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pentraxin-3 in familial Mediterranean fever patients during attack and attack-free periods

Abstract: In this study, we showed that PTX-3 levels, in both FMF attack and attack-free periods, were significantly higher than in the control group. Finally, PTX-3 may be a promising biomarker for FMF diagnosis and may predict FMF attacks (Tab. 2, Fig. 2, Ref. 18).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Higher ESR, CRP, fibrinogen, white blood cell count, and serum amyloid A (SAA) are expected results in active FMF disease compared to the attack-free period. 8 , 9 However, in a systematic review investigating APR used for FMF diagnosis, Erer et al reported that there was no effective APR to diagnose FMF disease. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Higher ESR, CRP, fibrinogen, white blood cell count, and serum amyloid A (SAA) are expected results in active FMF disease compared to the attack-free period. 8 , 9 However, in a systematic review investigating APR used for FMF diagnosis, Erer et al reported that there was no effective APR to diagnose FMF disease. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Higher ESR, CRP, fibrinogen, white blood cell count, and serum amyloid A (SAA) are expected results in FMF disease compared to the attack-free period [17,18]. However, in a systematic review investigating acute phase reactants used for FMF diagnosis, Erer et al reported that there was no effective acute phase reactant to diagnose FMF disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…There are other new candidate biomarkers for FMF in the literature [17,[24][25][26][27][28][29][30][31]. Pentraxin-3, omentin, fetuin, calprotectin, serum amyloid A, CD144 + , and CD146 + as circulating endothelial microparticles, endocan, chitotriosidase, serum matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1, S10012A and resolvin D1 has been investigated and had promising results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PTX3 levels were low in FMF patients with sufficient vitamin D status. Gok et al [4] determined that the PTX-3 level was higher in young adults in the attackfree period compared to the control, and PTX-3 had a sensitivity of 90% at a threshold value of 0.696 ng/mL. In the present study, we divided the patients into two groups according to cut-off value (0.640) for PTX-3, we found that vitamin D levels were significantly lower in the patient group with subclinical inflammation.…”
Section: It Has Been Suggested That Low Vitamin D Levels In Patients With Fmf May Induce Subclinical Inflammation Since Vitamin D Has An mentioning
confidence: 99%
“…PTX-3 levels were found to be higher in patients with FMF during attack and attack-free periods compared to control despite the use of colchicine. Some researchers have suggested that PTX-3 can be an indicator of subclinical inflammation [4][5][6]. Subclinical inflammation increases the risk of developing complications such as anemia, heart disease, and amyloidosis in patients with FMF.…”
Section: Introductionmentioning
confidence: 99%